A macroeconometric model of the Chinese economy - Duo Qin; Marie Anne Cagas; Geoffrey Ducanes; Xinhua He (Queen Mary University of London, Department of Economics, 2006)
This paper describes a quarterly macroeconometric model of the Chinese economy. The model comprises household consumption, investment, government, trade, production, prices, money, and employment blocks. The equilibrium-correction form is used for all the behavioral equations and the general\~Aâ exteuro~â exteuro™simple dynamic specification approach is adopted. Great efforts have been made to achieve the best possible blend of standard long-run theories, country-specific institutional features and short-run dynamics in data. The tracking performance of the model is evaluated. Forecasting and empirical investigation of a number of topical macroeconomic issues utilizing model simulations have shown the model to be immensely useful.
Keywords: C51; E17; 330; Macroeconometric model; Chinese economy; Forecasts; Simulations